Association of vitamin D deficiency and frailty: A systematic review and meta-analysis. (December 2016) - Zhou, Jianghua; Huang, Pan; Liu, Ping; Hao, Qiukui; Chen, Shangping; Dong, Birong; Wang, Jiang
Highlights: The meta-analysis intends to describe the association between low 25(OH)D and frailty. The association between frailty and lowest levels of 25(OH)D was significant. Vitamin D supplementation may improve the status of frailty in the elderly. Abstract: There is a biologically plausible association between low vitamin D, specifically serum 25-hydroxyvitamin D [25(OH)D] level, and frailty. We conducted a systematic review and meta-analysis to describe the association between low 25(OH)D level and frailty. We searched literature in OVID (Medline), EMBASE, Web of Knowledge and Cochrane CENTRAL Library Issue in May 2016, for cohort studies evaluating association of low 25(OH)D level with the risk of frailty. Studies were reviewed in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses(PRISMA) guidelines. A total of seven studies(17, 815 participants)were eligible in our study. The prevalence of frailty ranged from 3.9% to 31.9%. The pooled OR of frailty for the lowest versus the highest level of vitamin D was 1.27 (95% CI = 1.17–1.38, I 2 = 59%), suggesting that low level of vitamin D was significantly associated with the risk of frailty. In addition, results of subgroups analysis indicated that low level of vitamin D was significantly associated with the risk of frailty in female (pooled OR = 1.27, 95% CI = 1.15–1.40). Similar result was also found when frailty was defined by the Fried criteria or the modified Fried criteria (pooled OR = 1.25, 95% CI = 1.14–1.37), and FRAIL scale (pooled OR = 1.55, 95% CI = 1.07–2.25). Compared to the highest level of 25(OH)D, the association between frailty and the lowest level of 25(OH)D was significant in our study.